Histopathology of hepatocellular carcinoma - Manuel Schlageter; Luigi Terracciano; Salvatore D’Angelo; Paolo Sorrentino (2014)
Hepatocellular carcinoma (HCC) is currently the sixth most common type of cancer with a high mortality rate and an increasing incidence worldwide.Its etiology is usually linked to environmental, dietary or lifestyle factors.HCC most commonly arises in a cirrhotic liver but interestingly an increasing proportion of HCCs develop in the non-fibrotic or minimal fibrotic liver and a shift in the underlying etiology can be observed.Although this process is yet to be completely understood, this changing scenario also has impact on the material seen by pathologists, presenting them with new diagnostic dilemmas.Histopathologic criteria for diagnosing classical, progressed HCC are well established and known, but with an increase in detection of small and early HCCs due to routine screening programs, the diagnosis of these small lesions in core needle biopsies poses a difficult challenge.These lesions can be far more difficult to distinguish from one another than progressed HCC, which is usually a clear cut hematoxylin and eosin diagnosis.Furthermore lesions thought to derive from progenitor cells have recently been reclassified in the WHO.This review sum-marizes recent developments and tries to put new HCC biomarkers in context with the WHOs reclassification.Furthermore it also addresses the group of tumors known as combined hepatocellular-cholangiocellular carcinomas.